2007
DOI: 10.2174/1874192400701010008
|View full text |Cite
|
Sign up to set email alerts
|

Statin-Induced Increase in HDL-C and Renal Function in Coronary Heart Disease Patients§

Abstract: Background:Little is known about the potential of statin-induced high-density lipoprotein cholesterol (HDL-C) increase to improve renal function in coronary heart disease (CHD) patients. Methods and Results:In this post hoc analysis of the GREek Atorvastatin and Coronary heart disease Evaluation (GREACE) Study we investigated the effect of HDL-C increase after statin treatment on renal function. From a total of 1,600 patients, 880 were on various statins (mainly atorvastatin) and 720 were not. Other secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Also, the amount change of HDL-C was identified as a significant factor influencing changes in the eGFR during pitavastatin treatment; therefore, the increase of HDL-C might be attributed to the increase of the eGFR. In fact, the results of sub-analysis of the GREek Atorvastatin and Coronary-heart-disease Evaluation (GREACE) study suggested a relation between increased serum HDL-C and increased eGFR following atorvastatin treatment 21) . The antioxidant effects of HDL-C were considered to possibly underlie this correlation 22) ; however, further analysis is needed to clarify the mechanism underlying the increase of the eGFR induced by pitavastatin.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the amount change of HDL-C was identified as a significant factor influencing changes in the eGFR during pitavastatin treatment; therefore, the increase of HDL-C might be attributed to the increase of the eGFR. In fact, the results of sub-analysis of the GREek Atorvastatin and Coronary-heart-disease Evaluation (GREACE) study suggested a relation between increased serum HDL-C and increased eGFR following atorvastatin treatment 21) . The antioxidant effects of HDL-C were considered to possibly underlie this correlation 22) ; however, further analysis is needed to clarify the mechanism underlying the increase of the eGFR induced by pitavastatin.…”
Section: Discussionmentioning
confidence: 99%
“…The IDEAL (Incremental Decrease in End Points Through Aggressive Lipid Lowering) [42,43] and TNT (Treating to New Targets) trials [44,45] demonstrate that both low (10 mg/day) and high (80 mg/day) doses of atorvastatin reduced the risk of non-fatal myocardial infarction by 17-22% (p < 0.02). [42][43][44][45] Sub-studies of the GREACE (GREek Atorvastatin and Coronary-heart-disease Evaluation) [45][46][47][48], TNT (Treating to New Targets) [43,[49][50][51] and PROVE-IT (PRavastatin Or atorVastatin Evaluation and Infection Therapy) [52][53][54] trials showed similar results of atorvastatin reduced cardiac events but not only patients without diabetes but also in those with diabetes. Those studies included 15-25% of patients with diabetes.…”
Section: Statins Can Improve Dyslipidemia In Type 2 Diabetes and Resmentioning
confidence: 95%
“…In the GREACE sub-study, which compared to physicians'standard care [47], atorvastatin significantly reduced the relative risk of total mortality and cardiac moratility and morbidity (coronary mortality, coronary morbidity, and stroke). Furthermore, atorvastatin improved renal function [47] and liver function [46]. Of interest, patients with non-alcoholic fatty liver disease, statins (atorvastatin 24 mg/day) improved liver function, although liver injury was worsen in others without statin treatment for dyslipidemia.…”
Section: Statins Can Improve Dyslipidemia In Type 2 Diabetes and Resmentioning
confidence: 99%
See 1 more Smart Citation
“…In the GREACE study, various statin treatments (mainly atorvastatin) over 3 years significantly increased eGFR by 9.8% ( P < 0.0001, n = 880). Multiple regression analysis showed that every 5% statin-induced HDL cholesterol increase significantly and independently contributed to eGFR improvement 59. Furthermore, in patients with early diabetic nephropathy, pitavastatin 1 mg/day (n = 10) significantly reduced urinary albumin excretion and urinary liver-type fatty acid-binding protein (L-FABP), which reflected the extent of tubulointerstitial damage 60…”
Section: Clinical Studies Of Pitavastatinmentioning
confidence: 99%